Experimental evaluation of the near-field and far-field heating of focused ultrasound using the thermal dose concept - Filippou, Antria; Drakos, Theocharis; Giannakou, Marinos; Evripidou, Nikolas; Damianou, Christakis A. (My University, 2021)
Conventional motion algorithms utilized during High Intensity Focused Ultrasound (HIFU) procedures usually sonicate successive tissue cells, thereby inducing excess deposition of thermal dose in the pre-focal region. Long delays (~60 s) are used to reduce the heating around the focal region. In the present study the experimental evaluation of six motion algorithms so as to examine the required delay and algorithm for which the pre-focal (near-field) and post-focal (far-field) heating can be reduced using thermal dose estimations is presented.
Keywords: HIFU; Navigation algorithms; Near and far-field